A User-Based Method To Test The Usability of University of Zakho Website - Ahmed, Nawzat S. (Science Journal of University of Zakho, 2019)
Websites developed for an organisation, especially a university, always need maintenance and improvements to increase user satisfaction and to provide an environment that provides up-to-date information and services in efficient ways. Unfortunately, academic websites are often designed depended on the structure and objectives of an organisation, rather than on whether students, lecturers, and administrative staff find the website usable. This leaves the website users’ needs and expectations unsatisfied. The University of Zakho (UoZ), a public university in the Kurdistan Regional Government, is developing its website to include most of the information required. However, the usability of this website still needs to be checked to know whether or not it satisfies users. This study employs a user-based method to get the rate of usability satisfaction from the perspective of students and academic staff, and it investigates whether the occupation has significant impacts on usability satisfaction. This method is achieved by using a Website Analysis and Measurement Inventory (WAMMI) questionnaire, which is including five factors: attractiveness, controllability, helpfulness, efficiency, and learnability. The study offers recommendations and suggestions to the UoZ web developers for improving the website during the maintenance period. Further, this study proposes ways to enhance the academic websites usability.